PENERAPAN MODEL STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) PADA PEMBELAJARAN IPS SISWA KELAS IV SD AR RISALAH LUBUKLINGGAU - Veronica Anggraini; Syaprizal; Aren Frima (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to measure the achievement of social studies learning outcomes of fourth grade students at SDIQ Ar-Risalah Lubuklinggau. The research method used was a quasi-experimental design with a one group pre-test and post-test design. The population in this study consisted of all fourth grade students of SDIQ Ar-Risalah Lubuklinggau in the 2025/2026 academic year, totaling 101 students. The sample of this study was class IV Al-Fatih, consisting of 20 students. The data collection technique used was a test. The results showed that the average pre-test score of students was 53.7, while the average post-test score increased to 89.2. The data analysis technique used was the t-test. The result of the final test (post-test) at a significance level of α = 0.05 showed that Tcount > Ttable (9,5302 > 1.72913), which means that H₀ is rejected and Hₐ is accepted. Thus, it can be concluded that students’ learning outcomes after the implementation of the Student Teams Achievement Division (STAD) model in social studies learning for fourth grade students at SDIQ Ar-Risalah Lubuklinggau in the 2025/2026 academic year significantly achieved the minimum mastery criteria (KKTP).